Modern Analytical Facilities 2: A Review of Quality Assurance and Quality Control (QA/QC) Procedures for Lithogeochemical Data - Piercey, Stephen (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Quality assurance and quality control (QA/QC) are critical components of modern analytical geochemistry. A properly constructed QA/QC program identifies both the source of analytical error and provides a means of establishing confidence in and assessing limitations of analytical data. A QA/QC program involves monitoring precision, accuracy, and potential contamination from sampling to analysis. Precision can be monitored via the systematic insertion of sample, pulp, and analytical duplicates, and reference materials; the resulting data are subsequently evaluated using scatterplots, statistical tests (e.g. % relative standard deviation), Thompson-Howarth plots, and the average coefficient of variation (CVavg (%)). Accuracy is determined through the submission of reference materials and monitored using statistical tests (e.g. % relative difference, ttest) and Shewart control charts. Blanks test contamination and results are monitored using Shewart control charts.